Evaluation of Broth Disk Elution to Determine Colistin Susceptibility of Acinetobacter baumannii - Indar, Auravee; Ruekngam, Thaval; Pootong, Anek (Burapha Science Journal, 2026)
Acinetobacter baumannii is one of the major human pathogen causing nosocomial infections with highly drug-resistant to multiple classes of antibiotics. Antimicrobial susceptibility testing of colistin are more complex and high cost of commercial kit. In this study, we aimed to evaluate the colistin broth disk elution (CBDE) to determine in vitro colistin susceptibility against A. baumannii. A total of 98 isolates of A. baumannii were used in this study. Colistin MICs against A. baumannii were determined by CBDE and were compared with broth microdilution method. A very major error (VME), a major error (ME), categorical agreement (CA), essential agreement (EA), specificity, and sensitivity were analyzed. CBDE yield a CA and EA of 82.7 and 84.7%, respectively. Twelve VME (46.2%) and 5 ME (6.9%) were observed. Sensitivity and specificity of CBDE were 53.8 and 93.1%, respectively. CBDE was not suitable to detect colistin susceptibility of A. baumannii.